TIM proteins and microRNAs: distinct impact and promising interactions on transplantation immunity - Tao, Jialing; Shen, Xiaoxuan; Qian, Haiqing; Ding, Qing; Wang, Lihong (Frontiers in Immunology, 2024)
Achieving sustained activity and tolerance in of allogeneic grafts after post-transplantation remains a substantial challenge. The response of the immune system to “non-self” MHC-antigenic peptides initiates a crucial phase, wherein blocking positive co-stimulatory signals becomes imperative to ensure graft survival and tolerance. MicroRNAs (miRNAs) inhibit mRNA translation or promote mRNA degradation by complementary binding of mRNA seed sequences, which ultimately affects protein synthesis. These miRNAs exhibit substantial promise as diagnostic, prognostic, and therapeutic candidates for within the realm of solid organ transplantations. Current research has highlighted three members of the T cell immunoglobulin and mucin domain (TIM) family as a novel therapeutic avenue in transplantation medicine and alloimmunization. The interplay between miRNAs and TIM proteins has been extensively explored in viral infections, inflammatory responses, and post-transplantation ischemia-reperfusion injuries. This review aims to elucidate the distinct roles of miRNAs and TIM in transplantation immunity and delineate their interdependent relationships in terms of targeted regulation. Specifically, this investigation sought seeks to uncover the potential of miRNA interaction with TIM, aiming to induce immune tolerance and bolster allograft survival after transplantation. This innovative strategy holds substantial promise in for the future of transplantation science and practice.